2015
DOI: 10.3892/br.2015.424
|View full text |Cite
|
Sign up to set email alerts
|

Association investigation of BACH2 rs3757247 and SOD2 rs4880 polymorphisms with the type 1 diabetes and diabetes long-term complications risk in the Polish population

Abstract: Abstract. Genetic factors are indicated in the development of type 1 diabetes (DM1). Recently, nucleotide variants of BACH2 and SOD2 have been associated with this chronic condition. Therefore, the purpose of the present study was to investigate the contribution of BACH2 rs3757247 and SOD2 rs4880 (Ala16Val) polymorphisms to the risk of DM1 and diabetes long-term complications. Selected polymorphic variants of BACH2 and SOD2 were investigated in a group of 141 patients with DM1 and in a group of age, gender-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Wegner and cols. (28) investigated the rs3757247 SNP of the BACH2 gene in T1DM patients from Poland and did not find any significant association between the analyzed SNP and T1DM. In addition to the association with T1DM, other GWAS studies combined with meta-analyses have indicated that BACH2 SNPs are associated with other autoimmune diseases such as asthma (29), Cohn's diseases (30), coeliac disease (31), vitiligo (32), and Grave's disease (33).…”
Section: Discussionmentioning
confidence: 94%
“…Wegner and cols. (28) investigated the rs3757247 SNP of the BACH2 gene in T1DM patients from Poland and did not find any significant association between the analyzed SNP and T1DM. In addition to the association with T1DM, other GWAS studies combined with meta-analyses have indicated that BACH2 SNPs are associated with other autoimmune diseases such as asthma (29), Cohn's diseases (30), coeliac disease (31), vitiligo (32), and Grave's disease (33).…”
Section: Discussionmentioning
confidence: 94%
“…As mentioned above, inflammation may develop as a result of the formation of a deposit, or it may be a consequence of the intensification of oxidative stress processes observed in the course of urolithiasis [ 64 ]. Therefore, in our study we also analysed polymorphism located in SOD2 , encoding superoxide dismutase 2.…”
Section: Discussionmentioning
confidence: 99%
“…The increased activity of this enzyme leads to an enhancement in the level of H 2 O 2 , which is then removed by CAT. Therefore, numerous polymorphisms, that occur within this gene [especially c.47C > T— SOD2 (rs4880)], play an essential role in the development mechanism of various diseases, including cancers (breast, prostate, bladder, and cervical cancers), depression, coronary artery disease, and type 1 diabetes 35 , 44 – 48 . According to data provided by NCBI dbSNP, 39,247 SNPs in this gene have been registered.…”
Section: Discussionmentioning
confidence: 99%